The Biology of Cell-free DNA Fragmentation and the Roles of DNASE1, DNASE1L3, and DFFB - Han, Diana S.C. (Am J Hum Genet, 2020)
Cell-free DNA (cf.DNA) is a powerful noninvasive biomarker for cancer and prenatal testing, and it circulates in plasma as short fragments. To elucidate the biology of cf.DNA fragmentation, we explored the roles of deoxyribonuclease 1 (DNASE1), deoxyribonuclease 1 like 3 (DNASE1L3), and DNA fragmentation factor subunit beta (DFFB) with mice deficient in each of these nucleases. By analyzing the ends of cf.DNA fragments in each type of nuclease-deficient mice with those in wild-type mice, we show that each nuclease has a specific cutting preference that reveals the stepwise process of cf.DNA fragmentation. Essentially, we demonstrate that cf.DNA is generated first intracellularly with DFFB, intracellular DNASE1L3, and other nucleases. Then, cf.DNA fragmentation continues extracellularly with circulating DNASE1L3 and DNASE1. With the use of heparin to disrupt the nucleosomal structure, we also show that the 10 bp periodicity originates from the cutting of DNA within an intact nucleosomal structure. Altogether, this work establishes a model of cf.DNA fragmentation.